Gambaran Morfologi Sel Neutrofil Pada Pewarnaan Giemsa dengan Variasi Waktu Pada Larutan Pengencer Akuades - Muflihah, Ahdiah Imroatul; Destiawan, Rian Anggia; Wijaya, Anas Fadli; Widia, Leny Yulia; sufi, Queen Nurul; Azizah, Laila Camelia Nur; Makki, Alisa Alfiya (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Giemsa staining is a microscopic staining technique that aims to identify the morphology of leukocyte cell types. One of the methods that uses giemsa staining is the method of examining peripheral blood smear preparations which aims to evaluate the calculation of leukocyte type. The dyeing quality of giemsa is greatly influenced by the type of diluent material, namely buffer and aquadest. This study aims to determine the morphological picture of neutrophil cells in giema staining with time variations in aquadest diluent solution. The method of this study was to take blood from adults aged 20-25 years and had no history of illness as many as 24 samples. It was divided into 2 dilution groups, namely pH buffer 6.8 and aquadest, where each dilution was divided into 4 groups, namely group 1 soaking the peripheral blood smear preparation for 10 minutes, group 2 soaking the peripheral blood smear preparation for 20 minutes, group 3 soaking the peripheral blood smear preparation for 30 minutes, group 4 soaking the peripheral blood smear preparation for 40 minutes. Then a qualitative analysis was carried out, namely by comparing the background of the preparation and the morphology of neutrophil cells microscopically in each group. The results of this study are that microscopically groups 1 and 2 have a clear preparation background, while in groups 3 and 4 the preparation background is dirty and there are neutrophil granules and morphology in groups 1 and 2 show dark blue neutropnhil cells, groups 3 and 4 show purple and bluish-purple neutrophil cells. The conclusion of this study is based on the background of the preparation, and the morphology of neutrophil cells, the group that has the best results is groups 1 and 2. Key words : Aquadest, eosinophil cells, eutrophil cells, Giemsa staining